PENGARUH KINERJA PENYAMPAIAN JASA PENDIDIKAN DAN KEMAMPUAN ISTIMEWA TERHADAP KEUNGGULAN BERSAING (Suatu Survei Perguruan Tinggi Swasta di Wilayah Sumatera Bagian Selatan) - Desfiandi, Andi (Jurnal Manajemen dan Keuangan, 2010)
Recently, educational service sector in private higher education has been experiencing high competitiveness as the emerging of new departments which offer non-degree (D3) and under graduate degree (S1) by many universities. In additionally, quality of a university has important and critical factors in this high competitiveness. Existence of university will depend on this quality. This paper will explore studentâs perception regarding to services in education performance and extraordinary competence aligned with competitive advantage of south Sumatra universities. Descriptive and verification methods were deployed in this work in addition to modeling and solution technique. The methods will be used as an analysis tool which is known as structural equation modeling (SEM). In this work, private higher education (universities) in south Sumatra used as analysis unit, whilst students as observation unit. This paper shows that in order to improve competitive advantages, there two major aspects influence to services in education performance and unusual capability variables. The result of this work also demonstrates that unusual capability was figured by intangible asset and succeeding with stakeholder consideration as well as tangible asset.Keywords: Private higher education, performance, competitive advantage